2008
DOI: 10.1007/s10709-008-9270-x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness-related patterns of genetic variation in rhesus macaques

Abstract: The patterning of quantitative genetic descriptions of genetic and residual variation for 15 skeletal and six life history traits was explored in a semi-free-ranging group of rhesus macaques (Macaca mulatta Zimmerman 1780). I tested theoretical predictions that explain the magnitude of genetic and residual variation as a result of 1. strength of a trait's association with evolutionary fitness, or 2. developmental and physiological relationships among traits. I found skeletal traits had higher heritabilities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 59 publications
0
33
1
Order By: Relevance
“…The macaque results are consistent with this single human estimate. However, AFR in Finns was strongly influenced by maternal effects, while these are very small for female macaques (Blomquist 2009). An intriguing interpretation of this difference is that humans have evolved mechanisms to circumvent life-history trade-offs that are expressed in other female primates, possibly through the deliberate control and redistribution of resources within social groups, perhaps along kin lines, that results in the extension of parental effects to later ages (Cheverud & Moore 1994;Hawkes et al 1998;Kaplan & Robson 2002;Lee 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The macaque results are consistent with this single human estimate. However, AFR in Finns was strongly influenced by maternal effects, while these are very small for female macaques (Blomquist 2009). An intriguing interpretation of this difference is that humans have evolved mechanisms to circumvent life-history trade-offs that are expressed in other female primates, possibly through the deliberate control and redistribution of resources within social groups, perhaps along kin lines, that results in the extension of parental effects to later ages (Cheverud & Moore 1994;Hawkes et al 1998;Kaplan & Robson 2002;Lee 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, female AFR is known to be heritable in the study population, making genetic covariance with other life-history traits plausible (Blomquist 2009). A life-history trade-off will be indicated by a positive relationship between AFR and adult survival, because when all other factors are held constant, decreasing AFR will increase lifetime fitness (Roff 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The population is now composed of 1000 individuals divided into naturally-formed groups, allowing male dispersal and gene flow. The population shows no significant effect of inbreeding [35,42], and the variance in lifetime reproductive success between individuals is sufficient to create opportunities for selection [43]. Date of birth, natal and current group, maternal ID, and matriline membership are provided by the CPRC.…”
Section: Materials and Methods (A) Field Site And Subjectsmentioning
confidence: 99%
“…Several comparative studies in the 1980s (Gustafsson 1986; confirmed the expectation that traits closely associated with individual fitness would have lower heritabilities than traits less tightly linked with fitness. More recent work has shown that the low heritability of fitness traits can be accounted for by high levels of residual variance (especially environmental variance) rather than low levels of additive genetic variance (Price & Schluter 1991;Kruuk et al 2000;Wilson et al 2006), and that, when scaled correctly, fitness traits can have higher additive genetic variance than nonfitness traits (Houle 1992;Kruuk et al 2000;MerilĂ€ & Sheldon 2000;Barton & Keightley 2002;McCleery et al 2004;Coltman et al 2005;Blomqvist 2009). Since fitness traits are expected to have a more complex polygenic architecture than morphological or physiological traits (MerilĂ€ & Sheldon 1999), this may also result in greater opportunity for correlations between fitness traits and neutral marker loci.…”
Section: Quantitative Genetics Of Fitness and Nonfitness Traitsmentioning
confidence: 99%